2009
DOI: 10.1111/j.1540-8167.2009.01483.x
|View full text |Cite
|
Sign up to set email alerts
|

Selecting the Transthoracic Defibrillation Shock Directional Vector Based on VF Amplitude Improves Shock Success

Abstract: Choosing the defibrillation directional vector based on the largest VF amplitude improved shock success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Advantages of low‐energy shocks include shorter charge times, extended battery life, and possibly less myocardial damage. Nevertheless, in the modern era, charge time is not a major issue and higher energy shocks carry a greater probability of success 51,63,64 . Additional advantages of high‐energy shocks may include a higher probability of terminating inappropriately treated SVTs (for which the shock vector is suboptimal) and a slightly longer charging time that allows for ATP and favors self‐termination of nonsustained arrhythmias.…”
Section: Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Advantages of low‐energy shocks include shorter charge times, extended battery life, and possibly less myocardial damage. Nevertheless, in the modern era, charge time is not a major issue and higher energy shocks carry a greater probability of success 51,63,64 . Additional advantages of high‐energy shocks may include a higher probability of terminating inappropriately treated SVTs (for which the shock vector is suboptimal) and a slightly longer charging time that allows for ATP and favors self‐termination of nonsustained arrhythmias.…”
Section: Therapiesmentioning
confidence: 99%
“…Nevertheless, in the modern era, charge time is not a major issue and higher energy shocks carry a greater probability of success. 51,63,64 Additional advantages of highenergy shocks may include a higher probability of terminating inappropriately treated SVTs (for which the shock vector is suboptimal) and a slightly longer charging time that allows for ATP and favors self-termination of nonsustained arrhythmias. Until further data are available, maximum shock outputs, especially if threshold testing was not performed, should be programmed.…”
Section: Shocksmentioning
confidence: 99%
“…As previously mentioned, the energy required to defibrillate the www.intechopen.com heart is much smaller during short duration ventricular fibrillation then after prolonged episodes (Section 2.2). Brooks et al demonstrated that a shock delivered in a certain direction, chosen because there was high electrogram amplitude on it, was 5-9 times more likely to be successful than other direction without high electrogram amplitude (Brooks et al, 2009). In their study, two shock directions were used: orthogonal and lateral.…”
Section: Shock Location and Clinical Applications Of Shock Vectormentioning
confidence: 99%